Faktor-Faktor yang Mempengaruhi Penerapan Program Pelayanan Kesehatan Sekolah: Tinjauan Literatur - Ruri Virdiyanti; Sigit Mulyono (FORIKES, 2020)
Children are an age group that is vulnerable to exposure to various sources of disease. The implementation of the school health service program to help reduce morbidity in children, but always influenced by various factors so that the implementation is not optimal. The purpose of writing this article is to review the factors that influence the implementation of school health service programs. The method of this article was a literature review. Literature search was conducted by using an online database of BMC, Google Scolar, Proquest, and Science Direct. The results of the article searched found 4 articles that fit the inclusion criteria and then an analysis was found that the factors that could affect the implementation of the school health service program include: the ability to build teacher capacity, school infrastructure, teacher attitudes, the number of health workers in school, and community culture. The conclusion of this literature review requires further research on the influence of the role of community nurses on the implementation of health services in schools. Keywords: program; health service; school ABSTRAK Anak merupakan kelompok usia yang rentan untuk terpapar dengan berbagai sumber penyakit. Pelaksanaan program pelayanan kesehatan sekolah untuk membantu mengurangi angka kesakitan pada anak, namun selalu dipengaruhi oleh berbagai faktor sehingga pelaksanaan menjadi tidak optimal. Tujuan dari penulisan artikel ini adalah untuk meninjau faktor-faktor yang mempengaruhi penerapan program pelayanan kesehatan sekolah. Metode penulisan artikel adalah tinjauan literatur. Penelusuran literatur dilakukan dengan cara menggunakan online data base BMC, Google Scolar, Proquest, dan Science Direct. Hasil dari penelusuran artikel ditemukan 4 artikel yang sesuai dengan kriteria inklusi kemudian dilakukan analisis ditemukan bahwa fakor-faktor yang dapat mempengaruhi penerapan program pelayanan kesehatan sekolah antara lain: kemampuan membangun kapasitas guru, infrastruktur sekolah, sikap guru, jumlah tenaga kesehatan yang di sekolah, dan budaya komunitas. Kesimpulan dari tinjauan literatur ini diperlukan penelitian lebih lanjut mengenai pengaruh peran perawat komunitas terhadap pelaksanaan pelayanan kesehatan disekolah. Kata kunci: program; pelayanan kesehatan; sekolah